BILINGUAL PHONOLOGICAL SYSTEMS: UNRAVELING CROSS-LINGUISTIC INFLUENCE - Erkinjon Satibaldiyev (American Journals, 2023)
This article delves into the fascinating realm of bilingualism, focusing on the intricate interplay of phonological systems and the phenomenon of cross-linguistic influence. Exploring the complexities of bilingual speech production, this study investigates how individuals proficient in two languages navigate the phonological structures of each language. Through an analysis rooted in linguistic theory, psycholinguistics, and sociolinguistics, this research sheds light on the dynamic interactions within bilingual minds, uncovering the processes of phonological transfer, code-switching, and the impact of linguistic context on speech sound production.
Keywords: bilingualism; phonological systems; cross-linguistic influence; code-switching; phonological transfer; speech production